Impact of Huanglongbing (HLB) on grapefruit pectin yield and quality during grapefruit maturation. (April 2021) - Ferguson, Kyle; da Cruz, Maria A.; Ferrarezi, Rhuanito; Dorado, Christina; Bai, Jinhe; Cameron, Randall G.
Abstract: Huanglongbing (HLB) is a plant disease responsible for citrus tree decline, increased fruit drop, and deteriorated fruit quality. Citrus pectin is a billion-dollar industry which may be impacted by the HLB epidemic. We compared the physio-chemical properties of pectin in peel from HLB affected grapefruit collected from open-air trees against healthy grapefruit grown under protective screens (CUPS) at two developmental stages to ascertain HLB impacts on pectin. qPCR detected the causal agent of HLB, which determined if the tested fruit was healthy or non-healthy, and peel color and °Brix defined the fruit's maturity. Depending on the maturity of the HLB affected grapefruit there was between a 16%–25% decrease in pectin yield. HLB affected pectin showed significantly ( p < 0.05) increased arabinose, galactose, and in immature HLB affected pectin galacturonic acid sugars, resulting in a lower Homogalacturan/Rhamogalacturan I ratio and a lower degree of branching (DBr) compared to healthy peel pectin. HLB affected pectin had a 7% lower outside degree of methylation (DMoutside ) and a 28% decreased degree of blockiness (DB). The DB, absolute degree of blockiness (DBabs ), degree of methylesterification (DM), and DMoutside of HLB affected pectin indicates a larger number of non-endopolygalacturonase digestible GalA blocks suggesting HLB affected grapefruit may exhibit a more random methylation pattern. Grapefruit maturation resulted in a 20% increase in pectin yield with a 30% decrease in the pectin molecular weight. Understanding HLB's and fruit maturation impact on pectin will provide customers and manufacturers insight into how these factors impact the industry. Graphical abstract: Image 1 Highlights: The maturation of grapefruit decreased pectin's molecular weight. HLB decreased the degree of blockiness of the pectin samples. HLB decreases the Gal/Rha ratio of isolated pectin samples. HLB grapefruit pectin exhibits a more random charge distribution pattern.